OPTIMASI SISTEM LINING MOTOR ROKET PADAT RX1220 MELALUI PERUBAHAN KOMPOSISI MATERIAL LINER DAN METODE LINING (OPTIMIZATION OF LINING SYSTEM FOR RX1220 SOLID ROCKET MOTOR THROUGH IMPROVEMENT OF LINER MATERIAL COMPOSITION AND LINING METHOD) - Dewi, Wiwiek Utami (BRIN Publishing, 2014)
In 2013, as many as 21.42% of the RX1220 rocket motor production did not pass the radiographic testing due to air bubble presences within the liner layer (liner defects). In 2014, there are dimensional changes in the inside diameter of the rocket motor tube (107.5 mm to 107.1 mm). Lining process by using gravity casting method becomes more difficult to apply. Liner viscosity is considerably high for the lining method. The efforts to lower its viscosity had been done yet the result did not reach the expectation. The changes in liner composition and lining method were conducted to optimize the RX1220 lining process. The result was good. After the new compositionand improved method applied, no more liner defects in RX1220. All of RX1220 rocket motors were labeled QC pass from the radiographic testing.